2018
DOI: 10.1016/j.ebiom.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a 28-gene Hypoxia-related Prognostic Signature for Localized Prostate Cancer

Abstract: BackgroundHypoxia is associated with a poor prognosis in prostate cancer. This work aimed to derive and validate a hypoxia-related mRNA signature for localized prostate cancer.MethodHypoxia genes were identified in vitro via RNA-sequencing and combined with in vivo gene co-expression analysis to generate a signature. The signature was independently validated in eleven prostate cancer cohorts and a bladder cancer phase III randomized trial of radiotherapy alone or with carbogen and nicotinamide (CON).ResultsA 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 54 publications
6
126
0
Order By: Relevance
“…across cancers using the lme4 package (v1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For each feature of interest we compared a full model (i.e., a model with the feature of interest) to a null model (i.e.…”
Section: Linear Mixed-effect Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…across cancers using the lme4 package (v1. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For each feature of interest we compared a full model (i.e., a model with the feature of interest) to a null model (i.e.…”
Section: Linear Mixed-effect Modelsmentioning
confidence: 99%
“…Hypoxia can also be caused by changes in oxygen demand: altered tumour metabolism 6,7 can increase intra-cellular demand for oxygen, potentially extending hypoxia signalling to liquid tumours. The adaptation of tumour cells to this imbalance in oxygen supply and demand is associated with poor clinical prognosis in several cancer types, attributed at least in part to hypoxia-associated genomic instability and clonal selection [8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia has been well recognised as mediating resistance to radiotherapy 36,50,77 and is arguably the most established target not yet translated into the clinic 7 . Although studies in some cancer types showed hypoxia was an adverse prognostic feature following surgery 11,58,78,79 , we showed here its widespread importance for surgery-treated patients across tumour types. Importantly, the effect of hypoxia on surgical outcomes was comparable with other omics marker.…”
Section: Discussionmentioning
confidence: 53%
“…Five of the genes were prognostic in a single cohort and SPRED1 had no prognostic significance (Table III). We further compared TWIST1 to a recently published hypoxia-gene associated prognostic signature for prostate cancer [22]. The 28-gene prognostic signature was derived from the TCGA cohort, and had a significant proportion of genes absent in Sboner et al cohort.…”
Section: Resultsmentioning
confidence: 99%